Incidence and pattern of mycophenolate discontinuation associated with abnormal monitoring blood-test results: cohort study using data from the Clinical Practice Research Datalink Aurum. Issue 2 (2nd June 2022) - Nakafero, Georgina; Grainge, Matthew J; Card, Tim; Mallen, Christian D; Riley, Richard; van der Windt, Danielle; Fox, Christopher P; Taal, Maarten W; Aithal, Guruprasad P; Williams, Hywel C; Abhishek, Abhishek
Abstract: Objective: The aim was to examine the incidence and pattern of MMF discontinuation associated with abnormal monitoring blood-test results. Methods: Data from people prescribed MMF for common inflammatory conditions in the Clinical Practice Research Datalink were used. Participants were followed from the first MMF prescription. The primary outcome was drug discontinuation with an associated abnormal blood-test result within 60 days. Secondary outcomes were drug discontinuation for any reason and discontinuation associated with severely abnormal blood-test results within 60 days. Multivariable Cox regression was used to examine factors associated with the primary outcome. Results: The cohort included 992 participants (68.9% female, mean age 51.95 years, 47.1% with SLE) contributing 1885 person-years of follow-up. The incidence of MMF discontinuation associated with any (severely) abnormal blood-test results was 153.46 (21.07) per 1000 person-years in the first year of prescription and 32.39 (7.91) per 1000 person-years in later years. Of those patients prescribed MMF, 11.5% (1.7%) discontinued treatment with any (severely) abnormal blood-test results in the first year of prescription. After this period, a mean of 2.6% (0.7%) of patients discontinued treatment with any (severely) abnormal blood-test results per year. Increased serum creatinine and cytopenia were more commonly associated with MMF discontinuation than elevated liver enzymes. Chronic kidney disease stage 3 or higher was significantly associated with MMF discontinuation with any blood-test abnormalities [adjusted hazard ratio (95% CI) 2.22 (1.47, 3.37)]. Conclusion: MMF is uncommonly discontinued for blood-test abnormalities and even less often discontinued for severe blood-test abnormalities after the first year of prescription. Consideration can be given to less frequent monitoring after 1 year of treatment, especially in those without chronic kidney disease stage 3 or higher.